Development of a Universal Safety Behavior Management System for Coal Mine Workers - Jizu LI; Yuejiao LI; Xiaoguang LIU (Tehran University of Medical Sciences, 2015)
Background: In China, over 80% of all work-related deaths in the mining industry occur in coal mines and human factors constitute 85% of the direct causes of coal mine accidents, which indicates that significant shortcomings cur-rently exist in the safety behavior management of Chinese coal mine workers. We aimed to verify the impact of human psychological behavior in coal mine accidents systematically through experimental study, theoretical analysis and man-agement application. Methods: Four test instruments (Sensory and cognitive capacity test, Sixteen-Personal Factor Questionnaire, Symp-tom Checklist 90 Questionnaire and the supervisors' evaluation) were employed from November 2013 to June 2014 to identify unsafe behavior factors, the self-established Questionnaire of Safety Behavior Norms (QSBN) was also used to propose the safety behavior countermeasures of coal mine employees. Results: The mental health of most coal mine workers' is relatively poor. The sensory and cognitive capacity of those in different work posts varies greatly, as does the sense of responsibility. Workers are susceptible to external influ-ences, and score low in site management. When the 16-PF and SCL-90 sensory and cognitive assessments were com-bined, the psychological index predictive power was greatest for estimating sense of efficiency and degree of satisfac-tion in internal evaluations, while at the same time lowest for estimating control of introversion-extroversion and stress character. Conclusion: The psychological indicators can predict part of employee safety behavior, and assist a coal mine enter-prise to recruit staff, develop occupational safety norms and improve the working environment.